"If it is dreamable it is doable": the role of desired job flexibility in imagining the future. Issue 3 (14th March 2016) - Guglielmi, Dina; Chiesa, Rita; Mazzetti, Greta
Abstract : Purpose: – The purpose of this paper is to compare how the dimension of attitudes toward future that consists in perception of dynamic future may be affected by desirable goals (desired job flexibility) and probable events (probable job flexibility) in a group of permanent vs temporary employees. Moreover the aim is to explore the gender differences in respect to variables studied. Design/methodology/approach: – The data were collected using self-report questionnaires on a sample of 710 employees, of which 63 percent women, 57.2 percent permanent employees, and 42.8 percent fixed-term employees. Findings: – The results showed that probable job flexibility mediated the relationship between desired job flexibility and the perception of a dynamic professional future. In addition, the type of contract moderated the interaction effect of job mastery on the relationship between desired and probable flexibility. Job mastery, however, has a direct effect on probable flexibility only on women in fixed-term employment. Research limitations/implications: – The study presented some limitations: the data derived from the self-report questionnaires, respondents participated on a voluntary basis, and the research design was cross-sectional. Practical implications: – The results of this study could be used to influence guidance practitioners' decisions on the role of antecedents of future orientation (desired flexibility, probable flexibility, and job mastery) in designing programs and interventions for career management that also take gender into account. Originality/value: – Overall, these results provided some insight into the relationship between specific guidance actions and goal-oriented career planning.